2007
DOI: 10.1128/jvi.02800-06
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of Long Interspersed Element 1 by APOBEC3 Does Not Correlate with High-Molecular-Mass-Complex Formation or P-Body Association

Abstract: The human cytidine deaminase APOBEC3G (A3G) and other APOBEC3 proteins exhibit differential inhibitory activities against diverse endogenous retroelements and retroviruses, including Vif-deficient human immunodeficiency virus type 1. The potential inhibitory activity of human APOBEC proteins against long interspersed element 1 (LINE-1) has not been fully evaluated. Here, we demonstrate inhibition of LINE-1 by multiple human APOBEC3 cytidine deaminases, including previously unreported activity for A3DE and A3G.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
127
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 56 publications
14
127
1
Order By: Relevance
“…Expression of A3A in HEK293 cells to lower levels than those observed in the CD14 ϩ cells, however, caused marked genotoxicity. We show that endogenous A3A in CD14 ϩ and THP-1 cells localized to the cytoplasm, in contrast to the cell-wide localization observed for exogenous A3A in a variety of heterologous cell types (3,13,14,16,21,(27)(28)(29)(30)(31)(32)(33)(34). We further reveal that nuclear localization is necessary for A3A-mediated genotoxicity.…”
mentioning
confidence: 44%
See 2 more Smart Citations
“…Expression of A3A in HEK293 cells to lower levels than those observed in the CD14 ϩ cells, however, caused marked genotoxicity. We show that endogenous A3A in CD14 ϩ and THP-1 cells localized to the cytoplasm, in contrast to the cell-wide localization observed for exogenous A3A in a variety of heterologous cell types (3,13,14,16,21,(27)(28)(29)(30)(31)(32)(33)(34). We further reveal that nuclear localization is necessary for A3A-mediated genotoxicity.…”
mentioning
confidence: 44%
“…Previous studies of A3A localization have shown that untagged protein in HeLa cells (27), GFP-tagged protein in HeLa (28 -30) and HEK293T cells (29), or HA-tagged protein in HeLa (13,14,31,32), HEK293 (3), HEK293T (21,33,34), and U20S cells (16) has a cell-wide localization. A3A was determined to enter the nucleus of HeLa cells by passive diffusion (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is the APOBEC family of proteins that are cytidine deaminase and inactivate viral or LINE-1 DNA by introducing lethal mutations. [19][20][21][22][23] An RNA helicase MOV10 inhibits retrotransposition of LINE-1 by CONTACT Chen Liang …”
mentioning
confidence: 99%
“…One example is the APOBEC family of proteins that are cytidine deaminase and inactivate viral or LINE-1 DNA by introducing lethal mutations. [19][20][21][22][23] An RNA helicase MOV10 inhibits retrotransposition of LINE-1 by associating with LINE-1 RNP and diminishing LINE-1 RNA level. [24][25][26] A recent study by Goodier et al tested a panel of viral restriction factors and showed that many of them, including BST-2, ISG20, MAVS, Mx2 and ZAP, strongly reduce LINE-1 activity.…”
mentioning
confidence: 99%